240 vocabulary words 4th grade kids need to know - Beech, Linda Ward (New York : Scholastic Teaching Resources, 2004)
24 ready-to-reproduce packets that make vocabulary building fun and effective.
Keywords: English language -- Study and teaching -- Juvenile literature; Reading -- Study and teaching -- Juvenile literature